Approach to: the Patient with a Palpable Breast Mass - Rose Di Ioia (McGill Journal of Medicine)
Palpable breast masses are common reasons for presenting to the primary care or emergency clinic setting. Although most palpable masses are benign in etiology, the possibility of malignancy exists and may be anxiety-inducing to patients. A systematic approach to history-taking, to clinical breast examination and to imaging is important for the adequate evaluation of a palpable breast mass.